SOSIALISASI ANAK TK DI SEKOLAH AKIBAT PENERAPAN DISIPLIN OTORITER GURU (Penelitian Deskriptif pada TK PGRI 65 Gebangsari Semarang Tahun Ajaran 2008-2009) - Deliana, Sri Maryati (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
Background of this research was kindergarten teacher which in PBM (Learning Process Teachs) applies autoritary discipline though ought to a kindergarten teacher becomes fasilitator and having responsibility to create situation that can grow initiative, motivation and participant responsibility educates to learn. This research applies descriptive method Population in this rematch me kindergarten Â students of PGRI 65, with subjects 40. Sampling technique applies technics of population study. Variable in this research is socialization kindergarten student. Data collecting method by using Observation check list socialization of kindergarten .students. With three observers; Based on result of inferential research that applying of autoritary discipline Iearned haves an in with sociaIization children of because children will become more agresive. Based on result of this research suggested to learn kindergarten sudent teaching not to apply applying of autoritary discipline and teacher earns more patiently in facing behavior of kindergarten students.